Attributions for Racial Inequality among Southern, Rural African Americans - Jamie MacLennan (Journal of Public and Professional Sociology)
Researchers have discovered that African Americans are more likely than whites to attribute poverty and racial inequality to a combination of structural factors (such as discrimination) and individualistic factors (such as motivation). However, the percentage of respondents who exhibit this “dual consciousness” has varied substantially across studies. This is likely due to the different ways that poverty and racial inequality attributions have been measured, whether by closed-ended survey or open-ended interview questions. The following study seeks to supplement the existing literature with findings from 38 in-depth interviews with Southern, rural African Americans who live in an environment of concentrated poverty. Results show that a substantial majority (71%) exhibit a dual consciousness, providing explanations for poverty and racial inequality that are not included as options in existing survey items (including the General Social Survey). Implications for future design of survey items gauging poverty and racial inequality attributions are discussed.